2010
DOI: 10.4300/jgme-d-10-00012.1
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Express: A Pilot Program to Teach Anesthesiology Residents Communication Skills

Abstract: Background The Accreditation Council for Graduate Medical Education requires residency programs to teach 6 core competencies and to provide evidence of effective standardized training through objective measures. George Washington University's Department of Anesthesiology and Critical Care Medicine implemented a pilot program to address the interpersonal and communication skill competency. In this program, we aimed to pilot the Relationship Express model, a series of exercises in experiential … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 9 publications
(10 reference statements)
0
4
0
Order By: Relevance
“…Death and serious adverse events associated with anesthesia are rare, but when they occur, they usually arise suddenly and unexpectedly. Unlike physicians in some fields of medicine who may get ready in advance for BBN, anesthesiologists cannot avoid such situations, since they have to immediately announce the death or the occurrence of an intra-operative adverse event to the family of an anesthetized patient [ 11 ]. BBN in this context lacks the benefits of an ongoing professional relationship with the patient and is done with the patient’s anxious family.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Death and serious adverse events associated with anesthesia are rare, but when they occur, they usually arise suddenly and unexpectedly. Unlike physicians in some fields of medicine who may get ready in advance for BBN, anesthesiologists cannot avoid such situations, since they have to immediately announce the death or the occurrence of an intra-operative adverse event to the family of an anesthetized patient [ 11 ]. BBN in this context lacks the benefits of an ongoing professional relationship with the patient and is done with the patient’s anxious family.…”
Section: Discussionmentioning
confidence: 99%
“…Formal teaching does not often address communication skills and residents learn BBN “on the job” [ 11 ]. This training is highly variable and context specific, as many of the “teachers” themselves have had no formal training [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…18,33,34 Surgical residents also reported that OSCEs simulating EOL discussions in the intensive care unit are helpful and authentic. 35 Step 2-Targeted Needs Assessment While a limited number of previously published studies have described methods for teaching communication skills to anesthesiology residents, 36,37 no formal training programs specifically aimed at conducting CSD/GOCD have been reported for this group of trainees. Yet the anesthesiology milestones project specifically identifies "negotiates and manages patient and family conflicts in complex situations, including end-of-life issues" as a pertinent competence in the Interpersonal and Communication Skills domain.…”
Section: Step 1-problem Identification and General Needs Assessmentmentioning
confidence: 99%
“…The majority of curricula occur singularly 20,21 or at discrete intervals. 22 Full integration with assessment, experiential learning, and multiple communication domains have been cited as markers of a fully mature communication curriculum, 1 yet examples are rare. 23,24 Similar to other programs, our institution offered only a singular, stand-alone course in communication, centered around delivering bad news.…”
Section: Introductionmentioning
confidence: 99%